Performance Enhancement of Highway Subproject Management - Srisomboon, Wittaya; Wongwai, Narongrit; Malaikrisanachalee, Suphawut; Weravattanayingyong, Sopon (Engineering and Technology Horizons, 2021)
Highway subprojects have numerous activities; therefore, it is very complicated to allocate the annual budget. Nowadays, project prioritization criteria still need to be updated following engineering economic principles, in order that the budget allocation can actually fulfill the people’s requirements. This research applied multi-criteria decision analysis for developing project prioritization to analyze ten years subproject plan. The proposed method can save 16,324 million baht (17%) of annual government statement of expenditure, produce beneficial for 199,975 households, develop 4,503 community activities centers, solve 5,477 problems and develop 2,890 strategic routes.